Hubungan Jarak Tempuh dengan Indeks Prestasi Kumulatif Mahasiswa Prodi Pendidikan Matematika Angkatan 2021 - Gunadi, Gunadi; Tupulu, Nari (Papanda, 2025)
The purpose of this study was to determine whether there is a positive and significant relationship between commuting distance and the Grade Point Average (GPA) of students in the Mathematics Education Department, Faculty of Teacher Training, at Saint Augustine Hippo Catholic University. This research employed a quantitative approach, with data collected through questionnaires and documentation. The study was conducted at Saint Augustine Hippo Catholic University with a population of 2021 cohort students in the Mathematics Education Study Program. The research sample consisted of 18 students selected using a purposive sampling technique. Data analysis procedures included normality testing, linearity testing, homogeneity testing, and hypothesis testing using the t-test. The findings revealed a positive and significant relationship between commuting distance and the GPA of 2021 cohort Mathematics Education students. The results indicate that the farther the commuting distance students travel to campus, the lower the GPA they tend to achieve.